Aspect Shaper Facade Visual Quality Building On Jalan Pasar Besar Malang - Eni Zuliana; Jenny Ernawati; Herry Santosa (Syntax Literate, 2022)
Malang City is a a city designed by the Dutch Colonial nice and structured based on rule aesthetics caring environment facade visual quality building . Jalan Pasar Besar Malang is one of the the path that has score history and role important to development physical city of Malang. Research objectives this is for identify as well as describe aspect Influential visual quality significant to facade visual quality building on Jalan Pasar Besar Malang. Method used is quantitative with analysis linear regression . Based on analysis that has been conducted declared that aspect facade visual quality influential building significant to facade visual quality The building on Jalan Pasar Besar Malang is rhythm, coherence, scale, homogeneity, proportion and balance.